2022
DOI: 10.1111/dme.14829
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed diabetes: Prevalence and cardiovascular risk profile in a population‐based study of 52,856 individuals. The HUNT Study, Norway

Abstract: Aims We investigated the current extent of undiagnosed diabetes and prediabetes and their associated cardiovascular risk profile in a population‐based study. Methods All residents aged ≥20 years in the Nord‐Trøndelag region, Norway, were invited to the HUNT4 Survey in 2017–2019, and 54% attended. Diagnosed diabetes was self‐reported, and in those reporting no diabetes HbA1c was used to classify undiagnosed diabetes (≥48 mmol/mol [6.5%]) and prediabetes (39–47 mmol/mol [5.7%–6.4%]). We estimated the age‐ and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(76 reference statements)
3
4
0
Order By: Relevance
“…In agreement with previous studies,13 26 32 33 need indicators (perceived need for health services) in terms of high cholesterol was associated with UT2D. Some previous research15 16 18–20 25 26 30–32 showed a correlation between hypertension and obesity with UT2D versus no T2D, while we found negative associations with UT2D versus DT2D.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies,13 26 32 33 need indicators (perceived need for health services) in terms of high cholesterol was associated with UT2D. Some previous research15 16 18–20 25 26 30–32 showed a correlation between hypertension and obesity with UT2D versus no T2D, while we found negative associations with UT2D versus DT2D.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with previous studies,13 26 32 33 need indicators (perceived need for health services) in terms of high cholesterol was associated with UT2D. Some previous research15 16 18–20 25 26 30–32 showed a correlation between hypertension and obesity with UT2D versus no T2D, while we found negative associations with UT2D versus DT2D. Only cardiovascular disease was positively associated with DT2D, which again may be explained by a higher likelihood of being screened for T2D when attending to healthcare for cardiovascular disease management.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with some research [13][14][15] , in unadjusted analysis, we found a negative association between hypertension, cardiovascular disease, and undiagnosed T2D versus diagnosed T2D. Unlike some previous studies 22,31,32 , we did not find an association between elevated total cholesterol and undiagnosed T2D. However, we found a statistically significant positive association between elevated total cholesterol and diagnosed T2D.…”
Section: Discussionsupporting
confidence: 86%
“…The need factors associated with undiagnosed T2D include other chronic diseases 16 , hypertension status (not hypertension 13 , 14 , hypertension 17 , 18 , 29 , 30 ), obesity 17 19 , 21 , 22 , 28 , 31 , low HDL-C 31 , 32 , high triglycerides 31 , 32 , dyslipidaemia 22 , cardiovascular disease status (not heart disease 14 , cardiovascular disease 18 ), and perceived poor health 16 . The study aimed to estimate the prevalence and associated factors of undiagnosed T2D among people 18 years and older in Morocco.…”
Section: Introductionmentioning
confidence: 99%